PREJUDICE AND DISCRIMINATION OF DISABLED WOMAN IN RACHEL SIMON’S THE STORY OF A BEAUTIFUL GIRL - Mardhiyah, Luqyana; Kusuma, Agung Wiranata (Annual International Conferences on Language, Literature, and Media, 2023)
Disability has been one of the significant topics in the academic sphere. There are efforts from practitioners and organizations to bring equality for disabled persons. As in real life, people with disabilities often face prejudice and discrimination. This issue is also described in Rachel Simon's novel The Story of a Beautiful Girl (2011). This study analyzes the portrayal of prejudice and discrimination that the main character experiences and her actions to overcome the related challenges. This study uses Julie Smart's theory, which discusses prejudice and discrimination experienced by people with disabilities (PWD). This study uses literary criticism to evaluate and analyze literary works focusing on prejudice and discrimination. It is found out that the character with a disability experiences three types of prejudices: stereotypes, lowered expectations, and hypervisibility. Furthermore, discriminations portrayed in the novel include paternalism, marginality, and viewing PWD as an object of people without disabilities (PWOD). Overcoming prejudice and discrimination, the PWD shows their abilities to perform self-reliance in social and economic contexts, raising awareness in their society about the rights of people with disabilities to create mutual understanding.